50 Ischaemia and No Obstructive Coronary Artery Disease (INOCA): prevalence and predictors of coronary vasomotion disorders. (May 2019) - Ford, Tom; Good, Richard; Rocchiccioli, Paul; McEntegart, Margaret; Watkins, Stuart; Eteiba, Hany; Shaukat, Aadil; Lindsay, Mitchell; Robertson, Keith; Hood, Stuart; McGeoch, Ross; McDade, Robert; et al.
Abstract : Background: Ischemia and no obstructive epicardial coronary artery disease (INOCA) is a common clinical syndrome with distinct underlying causes. Objective: To evaluate the prevalence and predictors of microvascular and/or vasospastic angina (MVA/VSA) in an unselected cohort of angina patients referred for invasive coronary angiography with suspected ischaemic heart disease in whom obstructive coronary artery disease (CAD) is excluded. Methods: Prospective cohort study at two regional centres between November 2016 and December 2017 including patients with symptoms and/or signs of ischaemia prior to undergoing invasive coronary angiography (NCT03193294 ). Baseline risk was assessed (ASSIGN score) and validated questionnaires were completed prior to the angiogram including Rose angina, quality of life (EuroQOL [EQ-5D-5L]) and angina severity according to the Seattle Angina Questionnaire (SAQ). Patients with definite or probable angina without CAD [diameter stenosis <50% and/or FFR > 0.80] proceeded directly to assessment for disorders of coronary vasomotion. This involved an ad hoc interventional diagnostic procedure (IDP) using reference invasive tests for microvascular angina (MVA), vasospastic angina (VSA), both conditions or none. MVA and VSA groups were compared before logistic regression was performed to assess predictors of MVA and VSA. Results: Three hundred and ninety-one patients with angina were recruited before undergoing invasive coronary angiography during the study period. Overall, 185 (47%) of subjects had INOCA and 151 of these underwent an IDP. INOCA patients reported similar angina burden with worse quality of life than CAD subjects (EQ5D-5L index 0.60 v 0.65 units; P=0.041). The mean age of patients who underwent the IDP was 60.9 years, 74% were female and their median predicted 10-year IHD risk was 18.6% (10.6, 31.4). 78 subjects (52%) had isolated microvascular angina, 25 (17%) had isolated vasospastic angina, 31 (20%) had both (MVA & VSA) only 17 (11%) had non-cardiac chest pain. Myocardial bridging of coronary artery was found in 22 (15%). Multivariate predictors of MVA included typical angina, inducible ischaemia but traditional cardiovascular risk factors were not associated. Smoking and age were independent predictors of VSA. Conclusion: The majority of patients with symptoms and/or signs of ischemia and no obstructive disease have a diagnosis of microvascular and/or vasospastic angina. Traditional cardiovascular risk scores have limited discrimination for disorders of coronary vasomotion. Conflict of Interest: Nil